Repository for: Genetic footprints of a rapid and large-scale range expansion: The case of cyclic common vole in Spain - Domínguez Villaseñor, Julio César (Zenodo, 2023)
Te repository contains the neccesary genetic data (microsatellite allele frequencies and GenBank accesion numbers for cytb haplotypes) to be able to replicate the analyses performed in the manuscript. Funding provided by: Ministerio de Economía y Competitividad Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100003329 Award Number: CGL2011-30274 Funding provided by: Ministerio de Economía y Competitividad Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100003329 Award Number: CGL2015-71255-P Funding provided by: Ministerio de Economía y Competitividad Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100003329 Award Number: CGL2013-42451-P Funding provided by: Fundación BBVA Crossref Funder Registry ID: http://dx.doi.org/10.13039/100007406 Award Number: TOPIGEPLA Funding provided by: Fundación Agencia Aragonesa para la Investigación y el Desarrollo Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100008767 Award Number: PID2019-104835GB-100 Funding provided by: European Social Fund Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100004895 Award Number: SBPLY/16/180501/000205 Funding provided by: Junta de Comunidades de Castilla-La Mancha Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100011698 Award Number: SBPLY/16/180501/000205